Effect of rearfoot valgus on biomechanics during barbell squatting: A study based on OpenSim musculoskeletal modeling - Lu, Zhenghui; Li, Xin; Rong, Ming; Baker, Julien S.; Gu, Yaodong (Frontiers in Neurorobotics, 2022)
Background: barbell squats are commonly used in daily training and rehabilitation. Injuries are not common when the posture is standard, but the wrong posture can lead to injuries. Valgus is a common foot abnormality that may increase the risk of injury during sports. The purpose of this study was to compare the biomechanics of lower limbs in normal foot and valgus patients during barbell squat; Methods: in this study, 8 subjects with normal foot shape and 8 subjects with foot pronation were enrolled. Independent sample T-test and one-dimensional parameter statistical mapping were used to compare and analyze the differences of lower extremity joint Angle, joint moment, and knee joint contact force between the two groups of subjects under 0%, 30%, and 70%1RM load; Results: the range of motion and joint moment of the hip, knee, and ankle on the sagittal plane were significantly larger in the subjects who underwent barbell squat (P < 0.05), and the knee valved in the deepest squat. In addition, valgus subjects showed greater standardized medial knee contact force with increased load; Conclusions: the pronation population showed a greater range of joint motion when performing barbell squats, and showed genu pronation and greater medial knee contact, which may increase the risk of injury. In addition, there was no sig-nificant difference in valgus Angle between people with valgus and people with normal foot shape during squatting, so barbell squatting may correct valgus to a certain extent.